Asset Performance Management in Plant Maintenance: Technical Framework and Implementation - Mohan Kumar Dalai (International Journal of Intelligent Systems and Applications in Engineering, 2026)
Asset-intensive sectors are also increasingly adopting the‌ use of Asset Performance Management (APM)‌ software to move from a reactive and execution-oriented, labor-intensive maintenance process to a risk-informed and engineered discipline. Reactive maintenance and scheduled preventive maintenance are inadequate for handling the‌ complexity and interdependency of industrial‌ systems․ One of the most relevant aspects of the‌ digital transformation of industry, fueled by the ubiquitous proliferation of sensors and data acquisition systems, is the evolution of‌ maintenance concepts from experience-driven to evidence-driven and predictive scheduling. APM software solutions converge operational data, analysis‌ models, and decision support‌ to optimally manage capital assets' portfolios. APM incorporates principles of reliability engineering, asset economics, and systems thinking to realize modern asset management strategies, including predictive maintenance, failure‌ mode and effects analysis, estimation of remaining useful life, and risk-based decision-making. Key functions include estimating asset health using degradation modeling, forecasting failure, interfacing with computerized maintenance management systems (CMMS), and providing analysis of‌ system‌ interdependencies. APM implementation requires cultural changes like embracing‌ data-driven decision-making and knowledge acquisition/management, along with continuously monitoring‌ performance. Results include‌ reductions of unplanned downtime‚ reduced maintenance costs of 10-40%‚ improved asset availability‚ and improved safety‌ performance․ Future directions include the use of artificial intelligence, digital twins, and Industrial Internet of Things platforms for more‌ advanced maintenance planning tools and adaptive decision-making in increasingly complex industrial environments.